Thermoelectric technology for IC engine waste energy harvesting: liquid cooling approach - Rahman, Mohammed Ataur (IJSER in Research & Publication, 2017)
Thermoelectric generators are all solid-state devices that convert heat into electricity. It contains no moving parts and is completely silent. The total heat supplied to the engine in the form of fuel, approximately 30 to 40% is converted into useful mechanical work; whereas the remaining heat is expelled to the environment through exhaust gases and engine cooling systems, resulting in serious environmental pollution. So, it is required to utilize waste heat into useful work. The technologies on waste heat recovery of exhaust gas from internal combustion engines (ICE) are invented as thermo electric generators (TEG) with finned type, Organic Rankine cycle (ORC) and Turbocharger. This paper has presented semi-conductive TEG and GO/Silica composite TEG. Finned and liquid cooling type cooling has been adopted in both of the TEG. The performance of both cooling approaches for semi-conductive TEG has been compared in experimentally for the engine speed in the range 1000-3000 rpm. The result shows that the liquid cooling TEG has 25% higher performance in terms of electric power generation than the finned type TEG. The liquid cooling TEG has exhibited higher performance at engine speed of 5000 rpm and it was developed 524 W which can be used to operate the air-condition system of the vehicle, could contribute to reduce the 7-10% of engine total fuel consumption and improve emission level by 7%.